2016
DOI: 10.1074/jbc.m116.716001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of Yeast Suppressor of Ty 4/5 (Spt4/5) Reveals the Importance of Nucleic Acid Interactions in the Prevention of RNA Polymerase II Arrest

Abstract: RNA polymerase II (RNAPII) undergoes structural changes during the transitions from initiation, elongation, and termination, which are aided by a collection of proteins called elongation factors. NusG/Spt5 is the only elongation factor conserved in all domains of life. Although much information exists about the interactions between NusG/Spt5 and RNA polymerase in prokaryotes, little is known about how the binding of eukaryotic Spt4/5 affects the biochemical activities of RNAPII. We characterized the activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 77 publications
13
83
0
Order By: Relevance
“…The stimulation of RNA chain elongation by NusG has been documented in vitro for bacterial (Burova et al, 1995), archaeal (Hirtreiter et al, 2010) and eukaryotic (Wada et al, 1998) transcription systems. The NTD is sufficient for these effects on elongation, but the structural elements that superimpose well between the bacterial NusG NTD and the archaeal Spt5 NTD (Figure 8C) are limited to ( i ) the beta sheet that comprises the RNAP-binding site, ( ii ) the conserved five amino acid loop that we implicate in the anti-backtracking action of E. coli NusG, and ( iii ) the N-terminus of the α-helix that follows this loop and possibly interacts with the single-stranded non-template DNA (Crickard et al, 2016). The lack of the strong conservation of the surface residues (Figure 8D) suggests that the anti-backtracking activity may be determined by the overall fold of the NusG NTD and is only weakly dependent on the nature of the individual amino acid side-chains, consistent with the mutational analysis of E. coli NusG (Mooney et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of RNA chain elongation by NusG has been documented in vitro for bacterial (Burova et al, 1995), archaeal (Hirtreiter et al, 2010) and eukaryotic (Wada et al, 1998) transcription systems. The NTD is sufficient for these effects on elongation, but the structural elements that superimpose well between the bacterial NusG NTD and the archaeal Spt5 NTD (Figure 8C) are limited to ( i ) the beta sheet that comprises the RNAP-binding site, ( ii ) the conserved five amino acid loop that we implicate in the anti-backtracking action of E. coli NusG, and ( iii ) the N-terminus of the α-helix that follows this loop and possibly interacts with the single-stranded non-template DNA (Crickard et al, 2016). The lack of the strong conservation of the surface residues (Figure 8D) suggests that the anti-backtracking activity may be determined by the overall fold of the NusG NTD and is only weakly dependent on the nature of the individual amino acid side-chains, consistent with the mutational analysis of E. coli NusG (Mooney et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…4C). Crickard et al recently reported that replacing six residues of Spt5, a yeast homolog of NusG, located on the same face as the SWHL NusG motif with alanines abolished Spt5 cross-linking to the NT DNA and its anti-arrest activity (31). Although it is uncertain if the altered surface residues (which are only weakly conserved) or more extensive structural changes (such as local refolding caused by altered core residues) lead to the observed phenotypes, it seems probable that the four-alanine substitution in NusG abolishes its anti-pausing activity by altering interactions with the NT DNA and not with the GL.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, the elongation factor Spt4/5 targets the same position on the Pol II cleft as p53, displaying a closed conformation within the context of an elongation complex (Gnatt et al 2001;Kostek et al 2006;Bernecky et al 2016). Importantly, Spt4/5 directly interacts with the clamp domain to both positively and negatively regulate Pol II elongation (Yamaguchi et al 1999;Bernecky et al 2016;Crickard et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that p53 could retain its ability to associate with DNA directly while in complex with Pol II. Perhaps this ability could allow p53 to mimic elongation factors Spt4/5 and NusG, which stabilize the upstream DNA and the nontemplate strand in the transcription bubble to help prevent Pol II backtracking (Herbert et al 2010;Chakraborty et al 2012;Bernecky et al 2016;Crickard et al 2016). Therefore, a conserved structural mechanism may be used by p53, Spt4/5, and NusG to modulate Pol II elongation activity.…”
Section: Discussionmentioning
confidence: 99%